The Antiarrhythmic Mechanisms of Flecainide in Catecholaminergic Polymorphic Ventricular Tachycardia - Li, Yukun; Peng, Xiaodong; Lin, Rong; Wang, Xuesi; Liu, Xinmeng; Bai, Rong; Ma, Changsheng; Tang, Ribo; Ruan, Yanfei; Liu, Nian (Frontiers in Physiology, 2022)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a severe yet rare inherited arrhythmia disorder. The cornerstone of CPVT medical therapy is the use of β-blockers; 30% of patients with CPVT do not respond well to optimal β-blocker treatment. Studies have shown that flecainide effectively prevents life-threatening arrhythmias in CPVT. Flecainide is a class IC antiarrhythmic drug blocking cardiac sodium channels. RyR2 inhibition is proposed as the principal mechanism of antiarrhythmic action of flecainide in CPVT, while it is highly debated. In this article, we review the current progress of this issue.